Administration of branched-chain amino acids increases the susceptibility to lipopolysaccharide-induced inflammation in young Wistar rats. Issue 78 (November 2019) - Wessler, Leticia B.; de Miranda Ramos, Vitor; Bittencourt Pasquali, Matheus Augusto; Fonseca Moreira, José Cláudio; de Oliveira, Jade; Scaini, Giselli; Streck, Emilio L.
Highlights: Metabolic crises and neurologic deterioration in MSUD are often caused by infection. Brain inflammation is related to brain dysfunction observed in MSUD. MSUD is associated with a more intense neuroinflammation induced by LPS infection. Abstract: Maple Syrup Urine Disease (MSUD) is an inborn error of the metabolism caused by defects in the branched a-ketoacid dehydrogenase complex (BCKDC), leading to the accumulation of branched chain amino acids (BCAAs) (leucine, isoleucine and valine). Patients with MSUD present a series of neurological dysfunction. Recent studies have been associated the brain damage in the MSUD with inflammation and immune system activation. MSUD patients die within a few months of life due to recurrent metabolic crises and neurologic deterioration, often precipitated by infection or other stresses. In this regard, our previous results showed that the inflammatory process, induced by lipopolysaccharide (LPS), associated with high levels of BCAAs causes blood-brain barrier (BBB) breakdown due to hyperactivation of MMPs. Thus, we hypothesize that the synergistic action between high concentrations of BCAAs (H-BCAAs) and LPS on BBB permeability and hyperactivation of MMPs could be through an increase in the production of cytokines and RAGE protein levels. We observed that high levels of BCAA in infant rats are related to increased brain inflammation induced by LPS administration. In addition, BCAA exposure led to an increase on brain RAGE expression of young rats. The brain inflammation was characterized by enhanced levels of interleukin 1 β (IL-1β), interleukin 6 (IL-6), tumor necrosis factor-α (TNF-α) and Interferon- γ (IFN-γ), and decreased content of interleukin-10 (IL-10). Therefore, MSUD is associated with a more intense neuroinflammation induced by LPS infection.